VEGETATION MORTALITY CAUSED BY FOREST FIRE IN A FRAGMENT IN THE AMAZONIACERRADO-PANTANAL ECOTONE: USE OF DRONES IN THE ASSESSMENT - Olivo-Neto, Antonio Miguel; Carniello, Maria Antonia (Floresta, 2024)
Forest fires can cause several impacts, among which is the mortality of vegetation. The present study evaluated the post-fire dynamics and mortality of the arboreal vegetation of a forest fragment in the southwest region of Mato Grosso, using satellite images, data collected on-site, and high-resolution aerial images, obtained with drone. The work also evaluated the drone efficiency to estimate mortality parameters compared with the data obtained on-site. The results showed that the vegetation was strongly impacted by the fire and its incidence and consequently, the highest vegetation mortality occurred in drier regions within the fragment. On-site data showed that 41.91% of the arboreal individuals died, while the drone estimated 37.37% mortality. The estimates made for the whole area, based on on-site data, indicated a total of 328 dead ind/ha, dead basal area (G) of 5.4196 m², and dead volume of 54.317 m³. Drone data showed a total of 292 dead ind/ha, G of 7.4260 m², and dead volume of 94.7573 m³. Comparing the two methods, the statistical analysis showed a difference between the values for the individuals’ number and volume, not differing the estimates for G. It is concluded that the fire caused an intense impact in the area and drone can help in this evaluation, being viable to estimate G values in forest areas as assessed, as it does not differ from the estimates made with data obtained in the field.